Lithium manganese iron phosphate composite material as well as preparation method and application thereof
By using +3-valent iron sources and non-+2-valent manganese sources, combined with spray drying and double sintering processes, and using specific carbon sources to form carbon packages, the problem of low gram capacity of lithium iron manganese phosphate materials is solved and its performance is significantly improved. Electrochemical properties.
Patent Information
- Application Number
- CN202411366902.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-20
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The existing lithium manganese phosphate materials have a low gram capacity and need to improve their electrochemical properties.
Using +3-valent iron source and non-+2-valent manganese source, lithium iron manganese phosphate composite materials are prepared through spray drying and double sintering processes, and starch, polypropylene and acetylene black are used as carbon sources to form a uniform layer during the sintering process. Carbon wrapping improves the uniformity and density of the material.
The gram capacity of the lithium iron manganese phosphate composite material is significantly increased, and its uniformity and density are enhanced, thereby improving the energy density and endurance of lithium-ion batteries.
Smart Images

Figure CN119330322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery positive electrode materials, and more specifically, to a lithium manganese iron phosphate composite material and a preparation method and application thereof. Background Art
[0002] Lithium iron manganese phosphate (LiMn x Fe 1-x Lithium iron phosphate (LiFePO4, referred to as LMFP) is a new type of phosphate lithium-ion battery cathode material prepared on the basis of lithium iron phosphate (LiFePO4, referred to as LFP), and is also an olivine-type cathode material. The crystal structure of lithium manganese iron phosphate is similar to that of lithium iron phosphate, and it has the characteristics of stable chemical properties and excellent safety performance. At the same time, the doped manganese element can increase the charging voltage of the material, increasing the charging voltage from 3.4V of lithium iron phosphate to 4.1V, which increases the battery energy density by 15-20%, which is conducive to further expanding the range of endurance. Therefore, LMFP has better safety performance than ternary materials and higher energy density than LFP, and may become a better choice for future cathode materials. However, the gram capacity of lithium manganese iron phosphate is still relatively low and needs to be improved.
[0003] When preparing and synthesizing lithium manganese iron phosphate, its raw materials are usually +2-valent iron source and +2-valent manganese source. However, the sintering atmosphere must be strictly controlled during the sintering process, otherwise the +2-valent iron source is easily oxidized to generate other impurities, which seriously affects the performance of the finished product. Using +3-valent iron source instead of +2-valent iron source can make it easier to control the sintering atmosphere. Therefore, it is necessary to use +3-valent iron source instead of +2-valent iron source to synthesize lithium manganese iron phosphate. The valence of manganese source is +2, +3, +4, +5, +6 and +7. Using only +2-valent manganese source is not conducive to broadening the selection of raw materials for lithium manganese iron phosphate.
[0004] Therefore, it is of great economic value to develop a method for preparing a lithium iron manganese phosphate composite material that utilizes a +3-valent iron source and a non-+2-valent manganese source and can increase the gram capacity of lithium iron manganese phosphate. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to provide a lithium manganese iron phosphate composite material and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a lithium iron manganese phosphate composite material, the preparation method comprising the following steps:
[0008] S1. mixing a first lithium source, a first iron source, a first manganese source, a first phosphorus source, a first doping metal source, a first carbon source and a first solvent to obtain a first mixed slurry, spray drying, and performing a first sintering to obtain a seed crystal;
[0009] S2. Mix the seed crystals obtained in step S1, the second lithium source, the second iron source, the second manganese source, the second phosphorus source, the second doping metal source, the second carbon source and the second solvent to obtain a second mixed slurry, spray dry, and perform a second sintering to obtain a manganese iron phosphate lithium composite material;
[0010] Wherein, the first iron source and the second iron source are both +3-valent iron sources, and the first manganese source and the second manganese source are both non-+2-valent manganese sources;
[0011] In step S1, the mass ratio of the sum of the amount of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is 1 mol:(3.0-7.5) g.
[0012] In the present invention, the first carbon source can not only reduce the +3 valent iron source and the non-+2 valent manganese source to divalent iron (Fe 2+ ) and divalent manganese (Mn 2+ ), promoting Fe 2+ and Mn 2+ It enters the crystal lattice to form the crystal structure of lithium iron manganese phosphate, and obtains a seed with high uniformity, consistency and crystallinity, which is beneficial to improve the gram capacity of the lithium iron manganese phosphate composite material prepared using the seed; the first carbon source can also decompose to form carbon during the sintering process, and evenly wrap around the seed, thereby enhancing the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed, and thus improving the gram capacity of the lithium iron manganese phosphate composite material.
[0013] In the present invention, when the mass ratio of the sum of the amount of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is too high (i.e., the amount of the first carbon source is too small), the +3-valent iron source and the non-+2-valent manganese source cannot be fully reduced to divalent iron (Fe 2+ ) and divalent manganese (Mn 2+ ), which cannot better promote Fe 2+ and Mn 2+ The carbon cannot be uniformly wrapped around the crystal seeds to obtain seeds with high uniformity, consistency and crystallinity, and the gram capacity of the lithium manganese iron phosphate composite material is greatly reduced. When the ratio of the sum of the amount of iron in the first iron source and the amount of manganese in the first manganese source to the mass of the first carbon source is too small (that is, the amount of the first carbon source is too much), the +3-valent iron source and the non-+2-valent manganese source will be excessively reduced to iron and manganese, which will hinder the Fe 2+ and Mn 2+It enters the crystal lattice to form the crystal structure of lithium iron manganese phosphate, and at the same time interferes with the formation of seed crystals, which has an adverse effect on the uniformity, consistency and crystallinity of the seed crystals, thereby destroying the stability, uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed crystals, and ultimately leads to a significant decrease in the gram capacity of the lithium iron manganese phosphate composite material.
[0014] Preferably, the mass ratio of the sum of the amounts of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is 1 mol:(3.0-7.1) g.
[0015] More preferably, the ratio of the sum of the amounts of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is 1 mol:(3.09-7.01) g.
[0016] Preferably, in step S1, the first carbon source is starch, polypropylene and acetylene black in a mass ratio of 1:(0.4-1.0):(0.6-1.0).
[0017] The reason why the present invention selects starch, polypropylene and acetylene black as the first carbon source and controls the mass ratio of starch, polypropylene and acetylene black to be 1:(0.4-1.0):(0.6-1.0) is that the carbon formed by the decomposition of starch, polypropylene and acetylene black in a suitable mass ratio is not only conducive to the reduction of the +3-valent iron source and the non-+2-valent manganese source, but also to the reduction of Fe 2+ and Mn 2+ It can enter the crystal lattice to form the crystal structure of lithium iron manganese phosphate and can also form a uniform, continuous and highly graphitized carbon layer on the surface of the seed crystal, thereby enhancing the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed crystal, thereby increasing the gram capacity of the lithium iron manganese phosphate composite material.
[0018] Starch, polypropylene and acetylene black commonly used in the art can be used in the present invention.
[0019] Preferably, in step S1, the temperature of the first sintering is 300-750°C.
[0020] More preferably, in step S1, the temperature of the first sintering is 350-650°C.
[0021] In the present invention, when the temperature of the first sintering is too high, after the second sintering is completed, the grains of the obtained lithium iron manganese phosphate composite material are likely to be too large, resulting in a longer transmission path of lithium ions, and the gram capacity of the lithium iron manganese phosphate composite material cannot be better improved; at the same time, when the temperature of the first sintering is too high, the crystal structure of the seed is easily damaged, such as lattice distortion and unnecessary phase change, and it is impossible to obtain a seed with higher uniformity, consistency and crystallinity, and the gram capacity of the lithium iron manganese phosphate composite material cannot be better improved. When the temperature of the first sintering is too low, the first carbon source cannot be better decomposed to form carbon uniformly wrapped around the seed, and the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed cannot be better enhanced, thereby failing to better improve the gram capacity of the lithium iron manganese phosphate composite material.
[0022] More preferably, in step S1, the temperature of the first sintering is 550-650°C.
[0023] Preferably, in step S1, the first sintering time is 3-15 hours.
[0024] Preferably, in step S1, the first sintering is performed under the protection of an inert gas.
[0025] More preferably, the inert gas is at least one of nitrogen, helium, neon and argon.
[0026] Preferably, in step S1, the molar ratio of the lithium element in the first lithium source, the iron element in the first iron source, the manganese element in the first manganese source, the phosphorus element in the first phosphorus source and the doped metal element in the first doped metal source is (1.00-1.06):(0.35-0.45):(0.55-0.65):(1.00-1.05):(0.01-0.04), and the molar ratio of the total molar amount of the iron element in the first iron source, the manganese element in the first manganese source and the doped metal element in the first doped metal source to the molar amount of the lithium element in the first lithium source is 1 mol:(1.00-1.06) mol.
[0027] Preferably, in step S1, the ratio of the total mass of the first lithium source, the first iron source, the first manganese source, the first phosphorus source, and the first doping metal source to the mass of the first solvent is (1-6):(5-9).
[0028] Preferably, in step S1, the D50 particle size of the first mixed slurry is ≤0.6 μm.
[0029] Since the present invention adopts a solid phase method to prepare the seed crystal, the consistency and stability of the first mixed slurry will affect the performance of the lithium manganese iron phosphate composite material. The first lithium source, the first iron source, the first manganese source, the first phosphorus source, the first doped metal source, and the first carbon source used in the present invention have the characteristics of high material density and high specific gravity. At this time, if the D50 particle size of the first mixed slurry is too large, the consistency and stability of the first mixed slurry will be reduced, and sedimentation problems will occur.
[0030] Preferably, in step S2, the molar ratio of the lithium element in the second lithium source, the iron element in the second iron source, the manganese element in the second manganese source, the phosphorus element in the second phosphorus source and the doped metal element in the second doped metal source is (1.00-1.06):(0.35-0.45):(0.55-0.65):(1.00-1.05):(0.01-0.04), and the molar ratio of the total molar amount of the iron element in the first iron source, the manganese element in the first manganese source and the doped metal element in the first doped metal source to the lithium element in the first lithium source is 1 mol:(1.00-1.06) mol.
[0031] Preferably, the molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:(0.1-9).
[0032] More preferably, the molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:(0.11-9).
[0033] Preferably, in step S2, the ratio of the sum of the amounts of iron in the second iron source and manganese in the second manganese source to the mass of the second carbon source is 1 mol:(3.0-14.0) g.
[0034] More preferably, in step S2, the ratio of the sum of the amounts of iron in the second iron source and manganese in the second manganese source to the mass of the second carbon source is 1 mol:(3.2-13.9) g.
[0035] Preferably, in step S2, the ratio of the total mass of the second lithium source, the second iron source, the second manganese source, the second phosphorus source, and the second doping metal source to the mass of the second solvent is (1-6):(5-9).
[0036] Preferably, in step S2, the temperature of the second sintering is 600-850°C.
[0037] Preferably, in step S2, the second sintering time is 3-15 hours.
[0038] Preferably, in step S2, the second sintering is performed under the protection of an inert gas.
[0039] More preferably, the inert gas is at least one of nitrogen, helium, neon and argon.
[0040] Preferably, in step S2, the D50 particle size of the second mixed slurry is ≤0.9 μm.
[0041] In the present invention, the D50 particle size of the first mixed slurry and the second mixed slurry is measured by Malvern Panalytical Laser Particle Sizer Mastersizer 3000.
[0042] Preferably, the first lithium source or the second lithium source is at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium nitrate, lithium oxalate, lithium acetate, and lithium phosphate.
[0043] Preferably, the first phosphorus source or the second phosphorus source is at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate.
[0044] Preferably, in step S2, the second carbon source is starch, polypropylene and acetylene black in a mass ratio of 1:(0.2-0.4):(1.0-1.8).
[0045] Preferably, the first solvent or the second solvent is water.
[0046] Preferably, the +3-valent iron source is at least one of ferric phosphate, ferric oxide, ferric hydroxide and ferric acetate.
[0047] Preferably, the non-+2-valent manganese source is at least one of manganese dioxide, manganese trioxide, and manganese tetraoxide.
[0048] In the present invention, the doping metal element in the first doping metal source includes but is not limited to at least one of Ti, Mg, Al, Ni and Nb.
[0049] Preferably, the first doping metal source or the second doping metal source is a magnesium source.
[0050] More preferably, the magnesium source is at least one of magnesium oxide, magnesium hydrogen phosphate, magnesium hydroxide and magnesium carbonate.
[0051] In a second aspect, the present invention provides a lithium manganese iron phosphate composite material prepared by the preparation method described in the first aspect.
[0052] In a third aspect, the present invention provides an application of a lithium manganese iron phosphate composite material in a lithium ion battery.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] In the present invention, the first carbon source can not only reduce the +3 valent iron source and the non-+2 valent manganese source to divalent iron (Fe 2+ ) and divalent manganese (Mn 2+ ), promoting Fe 2+ and Mn 2+ It enters the crystal lattice to form the crystal structure of lithium iron manganese phosphate, and obtains a seed with high uniformity, consistency and crystallinity, which is beneficial to improve the gram capacity of the lithium iron manganese phosphate composite material prepared using the seed; the first carbon source can also decompose to form carbon during the sintering process, and evenly wrap around the seed, thereby enhancing the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed, and thus improving the gram capacity of the lithium iron manganese phosphate composite material.
[0055] The reason why the present invention selects starch, polypropylene and acetylene black as the first carbon source and controls the mass ratio of starch, polypropylene and acetylene black to be 1:(0.4-1.0):(0.6-1.0) is that the carbon formed by the decomposition of starch, polypropylene and acetylene black in a suitable mass ratio is not only conducive to the reduction of the +3-valent iron source and the non-+2-valent manganese source, but also to the reduction of Fe 2+ and Mn 2+ It can enter the crystal lattice to form the crystal structure of lithium iron manganese phosphate and can also form a uniform, continuous and highly graphitized carbon layer on the surface of the seed crystal, thereby enhancing the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed crystal, thereby increasing the gram capacity of the lithium iron manganese phosphate composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a charge and discharge curve diagram of a button-type lithium-ion battery prepared using the lithium manganese iron phosphate composite material in Example 1. DETAILED DESCRIPTION
[0057] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0058] The experimental methods in the following examples and comparative examples without specifying specific conditions are generally carried out according to conventional conditions in the art or according to conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0059] In each embodiment and comparative example of the present invention, the use of reagents is as follows:
[0060] Starch, S818265-5kg, Maclean;
[0061] Polypropylene, P816225-5kg, McLean;
[0062] Acetylene black, C742510-5g, Aladdin;
[0063] Sucrose, S818046-5kg, Maclean;
[0064] Carbon nanotubes, C805971-5g, MacLean;
[0065] Graphene, G762015-25g, MacLean.
[0066] In the present invention, the D50 particle size of the first mixed slurry and the second mixed slurry is measured by Malvern Panalytical Laser Particle Sizer Mastersizer 3000.
[0067] Example 1
[0068] This embodiment provides a lithium manganese iron phosphate composite material, and the preparation method thereof comprises the following steps:
[0069] S1. 4.50 mol of the first lithium source Li2CO3 (332.5 g), 1.665 mol of the first iron source Fe2O3 (265.9 g), 5.4 mol of the first manganese source MnO2 (469.5 g), 9.00 mol of the first phosphorus source NH4H2PO4 (1035.3 g), 0.27 mol of the first doped metal source MgO (10.9 g), 43.9 g of the first carbon source and 2100 g of the first solvent pure water were added to a sand mill containing 2 kg of 0.6-0.8 mm zirconium beads and ground for 5 h to mix to obtain a first mixed slurry, at which time the D50 particle size of the first mixed slurry was 0.5-0.6 μm, spray dried (the inlet air temperature of the sprayer was set to 220°C, and the outlet air temperature was set to 100±5°C), sintered in a 500°C box furnace for 8 h under nitrogen protection for the first sintering, cooled, and obtained a seed crystal;
[0070] S2. The seed crystal obtained in step S1, 0.50 mol of the second lithium source Li2CO3 (36.95 g), 0.185 mol of the second iron source Fe2O3 (29.55 g), 0.60 mol of the second manganese source MnO2 (52.16 g), 1.00 mol of the second phosphorus source NH4H2PO4 (115.03 g), 0.03 mol of the second doping metal source MgO (1.21 g), 7.6 g of the second carbon source and 1700 g of the second solvent pure water are added to a sand mill containing 2 kg of 0.4-0.6 mm zirconium beads and ground for 2 h to obtain a second mixed slurry, at which time the second mixed slurry has a D50 particle size of 0.8-0.9 μm, spray dried (the inlet air temperature of the sprayer is set to 220°C, and the outlet air temperature is set to 90±5°C), sintered in a box furnace at 730°C for 8 h under nitrogen protection, and cooled to obtain a lithium manganese iron phosphate composite material;
[0071] in:
[0072] In step S1, the mass ratio of the sum of the amount of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is 1 mol:5.03 g;
[0073] In step S1, the first carbon source is starch, polypropylene and acetylene black in a mass ratio of 1:0.7:0.8;
[0074] In step S1, the molar ratio of the lithium element in the first lithium source, the iron element in the first iron source, the manganese element in the first manganese source, the phosphorus element in the first phosphorus source and the doping metal element in the first doping metal source is 1:0.37:0.6:1:0.03, and the molar ratio of the sum of the moles of the iron element in the first iron source, the manganese element in the first manganese source and the doping metal element in the first doping metal source to the molar ratio of the lithium element in the first lithium source is 1 mol:1 mol;
[0075] In step S1, the ratio of the total mass of the first lithium source, the first iron source, the first manganese source, the first phosphorus source, and the first doping metal source to the mass of the first solvent is 5.03:5;
[0076] In step S2, the mass ratio of the sum of the amount of the iron element in the second iron source and the manganese element in the second manganese source to the mass of the second carbon source is 1 mol:7.835 g;
[0077] In step S2, the second carbon source is starch, polypropylene and acetylene black in a mass ratio of 1:0.3:1.4;
[0078] In step S2, the molar ratio of the lithium element in the second lithium source, the iron element in the second iron source, the manganese element in the second manganese source, the phosphorus element in the second phosphorus source, and the doping metal element in the second doping metal source is 1:0.37:0.6:1:0.03, and the molar ratio of the total molar amount of the iron element in the second iron source, the manganese element in the second manganese source, and the doping metal element in the second doping metal source to the molar amount of the lithium element in the second lithium source is 1 mol:(1.00-1.06) mol;
[0079] In step S2, the ratio of the total mass of the second lithium source, the second iron source, the second manganese source, the second phosphorus source, and the second doping metal source to the mass of the second solvent is 1:7.24;
[0080] The molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:0.11.
[0081] Examples 2-3 and Comparative Examples 1-2
[0082] Example 2-3 and Comparative Example 1-2 provide different lithium manganese iron phosphate composite materials, which differ from Example 1 in that the amount of the first carbon source is different, and the rest is consistent with Example 1, as shown in the following table:
[0083] Table 1 Amount of the first carbon source in Examples 1-3 and Comparative Examples 1-2
[0084]
[0085] Examples 4-7 and Comparative Examples 3-6
[0086] Examples 4-7 and Comparative Examples 3-6 provide different lithium manganese iron phosphate composite materials, which differ from Example 1 in that the mass ratios of starch, polypropylene and acetylene black in the first carbon source are different, and the rest are consistent with Example 1, as shown in the following table:
[0087] Table 2 Mass ratio of starch, polypropylene and acetylene black in the first carbon source in Examples 1, 4-7 and Comparative Examples 3-6
[0088]
[0089] Examples 8-9 and Comparative Examples 7-8
[0090] Examples 8-9 and Comparative Examples 7-8 provide different lithium manganese iron phosphate composite materials, which differ from Example 1 in that the temperature of the first sintering in step S1 is different, and the rest are consistent with Example 1, as shown in the following table:
[0091] Table 3 The temperature of the first sintering in step S1 of Examples 1, 8-9 and Comparative Examples 7-8
[0092] The temperature of the first sintering in step S1 / °C Example 1 550 Example 8 350 Example 9 650 Comparative Example 7 750 Comparative Example 8 300
[0093] Comparative Example 9
[0094] This comparative example provides a lithium manganese iron phosphate composite material, which differs from Example 1 in that sucrose is used instead of starch, and the rest is consistent with Example 1.
[0095] Comparative Example 10
[0096] This comparative example provides a lithium manganese iron phosphate composite material, which differs from Example 1 in that carbon nanotubes are used instead of acetylene black, and the rest is consistent with Example 1.
[0097] Comparative Example 11
[0098] This comparative example provides a lithium manganese iron phosphate composite material, which differs from Example 1 in that graphene is used instead of acetylene black, and the rest is consistent with Example 1.
[0099] Performance Testing
[0100] The performance tests of the lithium iron manganese phosphate composite materials of each embodiment and comparative example are as follows:
[0101] (1) Preparation of button-type lithium-ion batteries
[0102] A1. The lithium iron manganese phosphate composite material and the conductive agent (acetylene black) of each embodiment or comparative example were placed in an oven, baked at 120 ° C for 4h, and then cooled in a drying container; then, the lithium iron manganese phosphate composite material, the binder (polyvinylidene fluoride), and the conductive agent (acetylene black) were weighed in a corresponding proportion of the lithium iron manganese phosphate composite material and the conductive agent (acetylene black) in a mass ratio of 80:10:10, and added to a 50mL small beaker, and then the binder solution (5% mass fraction of polyvinylidene fluoride in N-methylpyrrolidone solution) was added, and the agitator was stirred into a paste;
[0103] A2. Apply the paste evenly on the aluminum foil to obtain a single-sided surface density of 60g / m 2 The positive electrode sheet was then placed in a blast drying oven and dried at 120°C for 2 hours and pressed (the pressing density of the positive electrode sheet was 2.0 g / cm 3 ), cut into a circular positive electrode sheet with a diameter of 12 mm;
[0104] A3. In an argon atmosphere glove box, a button-type lithium-ion battery was assembled using a circular positive electrode sheet as the positive electrode, a lithium sheet as the negative electrode, a nickel mesh as the current collector, and a 1 mol / L LiPF6 solution in ethylene carbonate and ethyl methyl carbonate (EMC) with a volume ratio of 3:7 as the electrolyte.
[0105] (2) Gram capacity test
[0106] Under the condition of 25℃±2℃, the assembled button-type lithium-ion battery was placed on a battery test system (Blue Electric series battery test system) for charge-discharge cycle test; the test conditions were as follows: the charge and discharge rate was 0.1C, the voltage range was 2.5V-4.5V, and the 0.1C discharge capacity of each battery was recorded; the number of button-type lithium-ion batteries in each embodiment or comparative example was 5, that is, the experiment was repeated 5 times, the 0.1C discharge capacity data was averaged, and the gram capacity of the lithium iron manganese phosphate composite material was calculated according to the following formula:
[0107] Gram capacity of lithium iron manganese phosphate composite material (mAh / g) = average value of 0.1C discharge specific capacity (unit: mAh) / mass of lithium iron manganese phosphate composite material (unit: g);
[0108] The experimental results are shown in the following table:
[0109] Table 4 Gram capacity of lithium iron manganese phosphate composite materials of various embodiments and comparative examples
[0110]
[0111]
[0112] Figure 1 This is a charge and discharge curve diagram of a button-type lithium-ion battery prepared using the lithium manganese iron phosphate composite material in Example 1.
[0113] From Table 4 and Figure 1 It can be seen that in the present invention, the first carbon source can not only reduce the +3-valent iron source and the non-+2-valent manganese source to divalent iron (Fe 2+ ) and divalent manganese (Mn 2+ ) and promote Fe 2+ and Mn 2+ It enters the crystal lattice to form the crystal structure of lithium iron manganese phosphate, and obtains a seed with high uniformity, consistency and crystallinity, which is beneficial to improve the gram capacity of the lithium iron manganese phosphate composite material prepared using the seed; the first carbon source can also decompose to form carbon during the sintering process, and evenly wrap around the seed, thereby enhancing the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed, and thus improving the gram capacity of the lithium iron manganese phosphate composite material.
[0114] Specifically, by comparing Examples 1-3 and Comparative Examples 1-3, it can be seen that in the present invention, when the ratio of the sum of the amount of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is too high (i.e., the amount of the first carbon source is too small), the +3-valent iron source and the non-+2-valent manganese source cannot be fully reduced to divalent iron (Fe 2+ ) and divalent manganese (Mn 2+ ), which cannot better promote Fe 2+ and Mn 2+ The carbon cannot be uniformly wrapped around the crystal seeds to obtain seeds with high uniformity, consistency and crystallinity, and the gram capacity of the lithium manganese iron phosphate composite material is greatly reduced. When the ratio of the sum of the amount of iron in the first iron source and the amount of manganese in the first manganese source to the mass of the first carbon source is too small (that is, the amount of the first carbon source is too much), the +3-valent iron source and the non-+2-valent manganese source will be excessively reduced to iron and manganese, which will hinder the Fe 2+ and Mn 2+ It enters the crystal lattice to form the crystal structure of lithium iron manganese phosphate, and at the same time interferes with the formation of seed crystals, which has an adverse effect on the uniformity, consistency and crystallinity of the seed crystals, thereby destroying the stability, uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed crystals, and ultimately leads to a significant decrease in the gram capacity of the lithium iron manganese phosphate composite material.
[0115] By comparing Examples 1, 4-7 and Comparative Examples 3-9, it can be seen that the reason why the present invention selects starch, polypropylene and acetylene black as the first carbon source and controls the mass ratio of starch, polypropylene and acetylene black to be 1: (0.4-1.0): (0.6-1.0) is that the carbon formed by the decomposition of starch, polypropylene and acetylene black in a suitable mass ratio is not only conducive to the reduction of the +3-valent iron source and the non-+2-valent manganese source, but also to the reduction of the Fe 2+ and Mn 2+ It can enter the crystal lattice to form the crystal structure of lithium iron manganese phosphate and can also form a uniform, continuous and highly graphitized carbon layer on the surface of the seed crystal, thereby enhancing the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed crystal, thereby increasing the gram capacity of the lithium iron manganese phosphate composite material.
[0116] By comparing Examples 1, 8-11, it can be seen that in the present invention, when the temperature of the first sintering is too high, after the second sintering is completed, the grains of the obtained lithium iron manganese phosphate composite material are prone to be too large, resulting in a longer transmission path of lithium ions, and the gram capacity of the lithium iron manganese phosphate composite material cannot be better improved; at the same time, when the temperature of the first sintering is too high, the crystal structure of the seed is prone to damage, such as lattice distortion and unnecessary phase change, and it is impossible to obtain a seed with higher uniformity, consistency and crystallinity, and the gram capacity of the lithium iron manganese phosphate composite material cannot be better improved. When the temperature of the first sintering is too low, the first carbon source cannot be better decomposed to form carbon uniformly wrapped around the seed, and the uniformity and density of the lithium iron manganese phosphate composite material prepared using the seed cannot be better enhanced, thereby failing to better improve the gram capacity of the lithium iron manganese phosphate composite material.
[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a lithium manganese iron phosphate composite material, characterized in that: The preparation method comprises the following steps: S1. mixing a first lithium source, a first iron source, a first manganese source, a first phosphorus source, a first doping metal source, a first carbon source and a first solvent to obtain a first mixed slurry, spray drying, and performing a first sintering to obtain a seed crystal; S2. Mix the seed crystals obtained in step S1, the second lithium source, the second iron source, the second manganese source, the second phosphorus source, the second doping metal source, the second carbon source and the second solvent to obtain a second mixed slurry, spray dry, and perform a second sintering to obtain a manganese iron phosphate lithium composite material; Wherein, the first iron source and the second iron source are both +3-valent iron sources, and the first manganese source and the second manganese source are both non-+2-valent manganese sources; In step S1, the mass ratio of the sum of the amount of the iron element in the first iron source and the manganese element in the first manganese source to the mass of the first carbon source is 1 mol:(3.0-7.5) g.
2. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step S1, the first carbon source is starch, polypropylene and acetylene black in a mass ratio of 1:(0.4-1.0):(0.6-1.0).
3. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: In step S1, the temperature of the first sintering is 350-650°C.
4. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: Including at least one of the following (1)-(4): (1) In step S1, the first sintering time is 3-15 hours; (2) In step S1, the molar ratio of the lithium element in the first lithium source, the iron element in the first iron source, the manganese element in the first manganese source, the phosphorus element in the first phosphorus source and the doping metal element in the first doping metal source is (1.00-1.06):(0.35-0.45):(0.55-0.65):(1.00-1.05):(0.01-0.04), and the molar ratio of the total molar amount of the iron element in the first iron source, the manganese element in the first manganese source and the doping metal element in the first doping metal source to the molar amount of the lithium element in the first lithium source is 1 mol:(1.00-1.06) mol; (3) In step S1, the ratio of the total mass of the first lithium source, the first iron source, the first manganese source, the first phosphorus source, and the first doping metal source to the mass of the first solvent is (1-6):(5-9); (4) In step S1, the D50 particle size of the first mixed slurry is ≤0.6 μm.
5. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: Including at least one of the following (1)-(7): (1) In step S2, the mass ratio of the sum of the amount of the iron element in the second iron source and the amount of the manganese element in the second manganese source to the mass of the second carbon source is 1 mol: (3.0-14.0) g; (2) In step S2, the second carbon source is starch, polypropylene and acetylene black in a mass ratio of 1:(0.2-0.4):(1.0-1.8); (3) In step S2, the temperature of the second sintering is 600-850°C; (4) In step S2, the second sintering time is 3-15h; (5) In step S2, the molar ratio of the lithium element in the second lithium source, the iron element in the second iron source, the manganese element in the second manganese source, the phosphorus element in the second phosphorus source, and the doping metal element in the second doping metal source is (1.00-1.06):(0.35-0.45):(0.55-0.65):(1.00-1.05):(0.01-0.04), and the molar ratio of the total molar amount of the iron element in the first iron source, the manganese element in the first manganese source, and the doping metal element in the first doping metal source to the lithium element in the first lithium source is 1 mol:(1.00-1.06) mol; (6) In step S2, the ratio of the total mass of the second lithium source, the second iron source, the second manganese source, the second phosphorus source, and the second doping metal source to the mass of the second solvent is (1-6):(5-9); (7) In step S2, the D50 particle size of the second mixed slurry is ≤0.9 μm.
6. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: The molar ratio of the lithium element in the first lithium source to the lithium element in the second lithium source is 1:(0.1-9).
7. The method for preparing the lithium iron manganese phosphate composite material according to claim 1, characterized in that: Including at least one of the following (1)-(7): (1) The first lithium source or the second lithium source is at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium nitrate, lithium oxalate, lithium acetate, and lithium phosphate; (2) the first phosphorus source or the second phosphorus source is at least one of ammonium phosphate, diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid, and lithium dihydrogen phosphate; (3) The first solvent or the second solvent is water; (4) The +3-valent iron source is at least one of ferric phosphate, ferric oxide, ferric hydroxide, and ferric acetate; (5) The non-+2-valent manganese source is at least one of manganese dioxide, manganese trioxide, and manganese tetraoxide; (6) The first doping metal source or the second doping metal source is a magnesium source.
8. The method for preparing the lithium iron manganese phosphate composite material according to claim 7, characterized in that: The magnesium source is at least one of magnesium oxide, magnesium hydrogen phosphate, magnesium hydroxide and magnesium carbonate.
9. A lithium manganese iron phosphate composite material, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the lithium iron manganese phosphate composite material according to claim 9 in lithium ion batteries.
Citation Information
Patent Citations
Method for preparing battery grade ferromanganese phosphate
CN106981656A
Lithium iron manganese phosphate cathode material and preparation method and application thereof
CN111933915A
Carbon-coated lithium manganese iron phosphate material, preparation method thereof and battery
CN115744860A
Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
CN117682493A
Method for preparing lithium manganese iron phosphate, cathode material, and lithium-ion battery
US20230322557A1